Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada CV. Berkat Anugrah - Setiawan, Ferry; Kartika Dewi, A. A Sagung (E-Jurnal Manajemen, 2014)
Abstract Performance is the behavior of every person as a performance produced by the employee in accordance with its role within the company. Compensation and work environment is believed to affect employee performance in achieving the goals set. The higher compensation and improvement in the working environment, the higher the performance of employees. The purpose of this study was to determine whether the compensation and work environment is directly significant effect on employee performance. The population in this study were all employees at CV. Berkat Anugrah to the grace which amounts to 32 respondents. Data were collected by questionnaire technique. The data analysis technique used is multiple linear regression analysis using SPSS 15.0 for Windows. Based on the analysis results proved that the compensation and work environment positive and significant impact on the performance of employees directly CV. Berkat Anugrah. The implications of this study, is the employee's performance should be improved, especially in the case; work must comply with the standards, the work must reach the target, the ability to complete the work and attitude of employee cooperation in completing the work. Compensation should be improved, especially in terms of holiday allowance. The work environment must be improved in terms of working environment that can provide encouragement and morale high. Keywords: Compensation, Work Environment, Employee Performance.